Fuera Eisenhower! - Palabra Obrera (Palabra Obrera, 1960)
Volante llamando a un acto contra el viaje de Eisenhower a Argentina.
Keywords: Eisenhower, Dwight; Gobierno de Frondizi; Palabra Obrera; Antiimperialismo; Estudiantil - Universidad